Physiological profile and predictors of cycling performance in ultra-endurance triathletes - Whyte, G.; Lumley, S.; George, K.; Gates, P.; Sharma, S.; Prasad, K.; McKenna, W. J. (The Journal of Sports Medicine and Physical Fitness, 2000)
To report physiological profiles, and investigate the relationship between selected physiological variables and cycling performance in ultra-endurance triathletes. METHODS: Participants: ten male (mean+/-SD, age; 32+/-5 years) ultra-endurance triathletes participated in the study. Physiological profiles were compared with 10 male age-matched control subjects. Measures: left ventricular structure (wall thickness [LVPWd], internal diameter [LVIDd], and mass [LVM]) and function (diastolic filling, fractional shortening, and stroke volume [SV]) were assessed using standard M-Mode, 2D, and Doppler echocardiography. Maximal and sub-maximal exercise gas exchange responses were measured on-line during a maximal ramping cycle-ergometer exercise test. RESULTS: Ultra-endurance triathletes demonstrated significantly larger LVPWd, LVIDd, LVM, SV, VO2max anaerobic threshold (AT), and power to body-mass ratio compared with controls. Cycling performance for both Ironman and half Ironman were significantly correlated with LVPWd, LVM, and SV. LVIDd was significantly correlated Ironman cycle time alone. Oxygen consumption (VO2) at AT, percentage of VO2max at AT, and peak power to bodymass ratio were significantly correlated to bike finish time in the half Ironman, but not Ironman. CONCLUSIONS: The correlation between cycling performance, LVM and SV suggests that the more conditioned athletes may be better able to maintain a high cardiac output during prolonged cycling. Sub-maximal gas exchange responses are predictors of cycling performance for the half-Ironman but not the Ironman. These results suggest that other factors including the longer duration swim prior to the cycling component, may impact upon cycle performance.